FAMINE OF 1932-1933 AS A RESULT OF THE CRIME OF STALIN’S TOTALITARIANISM (THE 80TH ANNIVERSARY OF THE TRAGEDY OF THE UKRAINIAN PEOPLE) - Куць, О.М.; Головачева, К.Р. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2013)
The article is about a tragic chapter in the history of the Ukrainian people - an artificial famine, aimed by totalitarian Stalinist regime at curbing of the most powerful nation among not Russian nations of USSR - Ukrainian, eradication from its self-consciousness any sentiments or steps towards independence and self-development.